Edukasi Tentang Pengenalan Perangkat Keras dan Perangkat Lunak Pada Anak Usia Dini - Evi Purnamasari; Dwi Asa Verano (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
Education about hardware and software is very important to improve technological literacy. This study discusses the introduction of hardware components such as CPU, RAM, motherboard, mouse, keyboard, hard disk, and software such as operating systems and applications. Interactive technology-based learning methods are used to facilitate understanding. This study uses a qualitative approach with a descriptive analysis method to describe the application of observation and question and answer methods as education for introducing hardware and software to early childhood. Data were collected through structured interviews, participatory observation and document analysis. Data obtained through observation and interviews were analyzed qualitatively. To test the validity of the data, data triangulation was used, namely comparing the findings of observations, interviews and document analysis. The results of the study showed that this approach significantly increased students' interest and knowledge in learning. Practice-based learning has proven to be the key to improving students' technological literacy. In addition, increasing technological literacy is expected to help students be better prepared to face challenges in the digital era.